2015
DOI: 10.2112/jcoastres-d-13-00127.1
|View full text |Cite
|
Sign up to set email alerts
|

Future Sea Level Rise and Changes on Tides in the Patagonian Continental Shelf

Abstract: Luz Clara, M.; Simionato, C.G.; D'Onofrio, E., and Moreira, D., 0000. Future sea level rise and changes on tides in the Patagonian Continental Shelf. Journal of Coastal Research, 00(0), 000-000. Coconut Creek (Florida), ISSN 0749-0208.We investigate the effect of the future sea level rise (SLR) on the propagation of tides in the Patagonian Shelf by means of numerical simulations. Using a barotropic implementation of the Model for Applications at Regional Scales (MARS), we obtain solutions for scenarios which r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 60 publications
3
21
0
Order By: Relevance
“…In Mar del Plata, we find a lower increase of the MLWs and a greater decrease of the MHWs than in Buenos Aires, and there is no correlation between the changes in the tides and the river runoff as well as between the Residual percentiles series and extreme river discharge into the RdlP. Therefore, the observed tidal changes are produced by a different factor than in Buenos Aires such as changes in the thermohaline structure of the Brazil/Malvinas confluence region or the rise of the MSL, although for the latter studies have shown that greater increases of the MSL are required to produce significant changes in the tides (Luz Clara et al, 2015;Carless et al, 2016).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In Mar del Plata, we find a lower increase of the MLWs and a greater decrease of the MHWs than in Buenos Aires, and there is no correlation between the changes in the tides and the river runoff as well as between the Residual percentiles series and extreme river discharge into the RdlP. Therefore, the observed tidal changes are produced by a different factor than in Buenos Aires such as changes in the thermohaline structure of the Brazil/Malvinas confluence region or the rise of the MSL, although for the latter studies have shown that greater increases of the MSL are required to produce significant changes in the tides (Luz Clara et al, 2015;Carless et al, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…Tidal changes obtained from simulations under SLR scenarios depend not only on the SLR scenario and its spatial variability, but also on the stratification scheme and on whether land is allowed to flood (Pickering et al, 2012;Carless et al, 2016). Simulations of high end SLR scenarios (i.e., above 1 m) over the Patagonian shelf performed by Carless et al (2016) and Luz Clara et al (2015) showed an increase of the M2 amplitude in the coastal region of Mar del Plata and a decrease of its phase. We observe the opposite pattern during the last 40 years at this location.…”
Section: Tidal Analysismentioning
confidence: 97%
“…6) Repeat step 5) to calculate all DOVs of all crossover points. The same pass may be different for all cycles and the farthest distance of crossover points for the same ascending and descending arcs may be up to 1 km for T/P, Jason-1 and Jason-2 (Fu and Cazenave, 2000;Luz Clara, Simionato, D'Onofrio, & Moreira, 2015). So the mean position of crossover point for the same ascending and descending arcs should be determined.…”
Section: Determination Of Oceanic Dovsmentioning
confidence: 99%
“…In addition, hypothetical SLR scenarios were incorporated to assess further possible rise, (i.e., 1.0 and 2.0 m after , who added SLR of 1, 2, or 3 m in scenarios). Clara et al (2015) considered even 10 m of SLR to get insight into potential future SLR. In addition, a nodal factor of 18.6 years was included in the analyses, and hypothetical cases involving removal of the Siwha Dike were tested to assess the potential for restoration, with or without consideration of potential SLR.…”
Section: Slr Scenarios and Numerical Parametersmentioning
confidence: 99%
“…Van Maanen et al (2013) simulated the morphological evolution of a tidal embayment to explore its response to rising sea level for semi-circular idealized basin with a barrier, and found SLR affected the exchange of sediment between the different morphological elements. Besides the impacts on sedimentation, the tidal energy variations associated with SLR were deeply investigated (Clara et al, 2015) in a series of scenarios that www.JCRonline.org www.cerf-jcr.org represented the present and future conditions due to SLR.…”
Section: Introductionmentioning
confidence: 99%